Черномырдинки и техника комического у Михаила Зощенко - Anna Weigl (Studia Rossica Posnaniensia)
This article considers the sphere of linguistic humour, specifically the linguistic structure of the so-called ‘chernomyrdinki’. Chernomyrdinki are written fixations of spontaneous oral statements by Viktor S. Chernomyrdin, a Soviet and post-Soviet statesman (1938–2010), which have become aphorisms. Chernomyrdinki are regularly reproduced and have not lost their popularity. Chernomyrdinki are, for the most part, Chernomyrdin’s spontaneous reactions to typical questions from journalists. The task of this study is to show that the not fully conscious, spontaneous statements by V. Chernomyrdin and the speech of Mikhail Zoshchenko’s heroes, deliberately constructed by the author in the course of the creative process, have much in common in their techniques of the comic and are at times identical. This study is based on the classification of “humour” in the speech of the heroes of M. Zoshchenko, developed by Mikhail Kreps.